Novel Target Genes of RUNX2 Transcription Factor and 1, 25‐Dihydroxyvitamin D3. Issue 9 (September 2014) - Stephens, Alexandre S.; Morrison, Nigel A.
ABSTRACT The RUNX2 transcription factor is indispensable for skeletal development and controls bone formation by acting as a signaling hub and transcriptional regulator to coordinate target gene expression. A signaling partner of RUNX2 is the nuclear vitamin D receptor (VDR) that becomes active when bound by its ligand 1, 25‐dihydroxyvitamin D3 (VD3). RUNX2 and VDR unite to cooperatively regulate the expression of numerous genes. In this study, we overexpressed RUNX2 in NIH3T3 fibroblasts concomitantly treated with VD3 and show that RUNX2 alone, or in combination with VD3, failed to promote an osteoblastic phenotype in NIH3T3 cells. However, the expression of numerous osteoblast‐related genes was up‐regulated by RUNX2 and large‐scale gene expression profiling using microarrays identified over 800 transcripts that displayed a twofold of greater change in expression in response to RUNX2 overexpression or VD3 treatment. Functional analysis using gene ontology (GO) revealed GO terms for ossification, cellular motility, biological adhesion, and chromosome organization were enriched in the pool of genes regulated by RUNX2. For the set of genes whose expression was modulated by VD3, the GO terms response to hormone stimulus, chemotaxis, and metalloendopeptidase activity where overrepresented. Our study provides a functional insight into the consequences of RUNX2 overexpression and VD3 treatment in NIH3T3 cells in addition to identifying candidate genes whose expression is controlled by either factor individually or through their functional cooperation. J. Cell. Biochem. 115: 1594–1608, 2014. © 2014 Wiley Periodicals, Inc.